Cultural Factors of Aggression in the Public Field - Młodzik, Lilla (Political Preferences, 2019)
The analysis of literature on the subject indicates the occurrence of cultural stereotypes that hinder the adaptation to the conditions of the era of an information civilization. They are of a particular importance in the public sphere. Their main feature (disadvantage) is the stimulation of aggression in social relations, the manifestations of which deform the functioning of liberal democracy. Aggression as a cultural trait comes from the fear of losing identity and from the uncertainty. The dissemination of the patterns of liberal culture and thus the displacement of the restrictive culture are the ways of counteracting the negative phenomena associated with it. The development of this problem is the subject of this text.